2013
DOI: 10.1016/j.neuron.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Monkey Area MT Latencies to Speed Changes Depend on Attention and Correlate with Behavioral Reaction Times

Abstract: Selective visual attention is known to be associated with characteristic modulations of neuronal activity in early visual cortex, but there is only rare evidence showing that these neuronal modulations are directly related to attention-dependent behavioral improvements. Here, we describe a strong, transient increase in the response of neurons in the mediotemporal (MT) area to behaviorally relevant speed changes that is not only modulated by attention but also highly correlated with the animal's performance. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 56 publications
12
76
0
Order By: Relevance
“…It is suggested that common neuromodulatory systems are involved in regulating attention and cortical desynchronization (4,5), and attention may lead to a reduction in response latency (45). Indeed, attention-induced latency advance has been observed in monkey V4 (46,47) and MT (48), and the shorter latency of visual response correlates with faster reaction of the animal (47,48). Because selective attention may involve local desynchronization of neuronal activity along the visual pathway representing the attended stimulus (4,49), the cumulative effect revealed here may play a role in visual processing during selective attention.…”
Section: Brain State Modulation Of Response Latency In Various Sensorymentioning
confidence: 99%
“…It is suggested that common neuromodulatory systems are involved in regulating attention and cortical desynchronization (4,5), and attention may lead to a reduction in response latency (45). Indeed, attention-induced latency advance has been observed in monkey V4 (46,47) and MT (48), and the shorter latency of visual response correlates with faster reaction of the animal (47,48). Because selective attention may involve local desynchronization of neuronal activity along the visual pathway representing the attended stimulus (4,49), the cumulative effect revealed here may play a role in visual processing during selective attention.…”
Section: Brain State Modulation Of Response Latency In Various Sensorymentioning
confidence: 99%
“…100 Computational models confirm that multiplicative-gain type 101 increases in neuronal firing rates can produce a benefit when 102 decoding population activity (Cohen and Maunsell, 2009;Mitchell 103 et al, 2009;Ling et al, 2009). Attention also reduces the latency of 104 neuronal responses (Sundberg et al, 2012;Galashan et al, 2013), 105 which could potentially provide more information in a shorter 106 amount of time, thus facilitating a faster reaction. More intense or 107 higher contrast stimuli evoke shorter latency responses across 108 numerous visual areas (Bell et al, 2006;Raiguel et al, 1999; 109 Albrecht, 1995;Oram et al, 2002); thus attention, by reducing 110 response latencies, effectively makes a stimulus resemble a higher 111 contrast version of itself, similar to its effect on the contrast 112 response function measured in firing rate (Reynolds et al, 2000).…”
mentioning
confidence: 95%
“…272 Attention also shortens the latency of visual responses in area MT, 273 and this decrease in latency is associated with faster overall 274 reaction times (Galashan et al, 2013). Attention-induced changes 275 in synchrony also predict performance in attention tasks.…”
mentioning
confidence: 99%
“…For instance, directing attention to the motion of a stimulus, in terms of direction and speed, locally increases the firing rate (Treue and Maunsell, 1996) and the gamma power of the local field potential (Khayat et al, 2010) of neurons in motion-sensitive mediotemporal (MT) area, causes shrinkage of receptive fields around the attended stimulus (Womelsdorf et al, 2006a), and increases stimulus selectivity of single neurons (Wegener et al, 2004). As a consequence of attentional modulation, task-relevant motion changes are represented with shorter latency, and reaction times (RTs) become faster (Galashan et al, 2013). Corresponding findings have been obtained in other visual areas for features like color and form (McAdams and Maunsell, 1999; Reynolds et al, 1999; Fries et al, 2001; Taylor et al, 2005; Sundberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%